Changing Fortunes: Armaments and the U.S. Economy - Jonathan Nitzan; Robin Rowley; Shimshon Bichler (The Bichler and Nitzan Archives, 1989)
The present essay is the second in a series of four papers in which examine the political economy of armaments in recent decades. In this paper we focus on the `armament core' of large military producers which recently emerged as a powerful bloc within the big economy of the United States. The rise of this core was heightened by a gradual shift of large civilian companies toward the armament business. We argue that the decline of large U.S.-based corporations in civilian world markets since the late 1960s was both a stimulus to and a partial consequence of the increasing involvement with better investment opportunities in government-related activity, especially military production. The increasing significance of international developments inhibits the earlier effectiveness of the U.S. government in assisting corporations based in the United States with its own military spending.
Keywords: 330; armament; civilian business; military bias; military contractors; profit; subsidies; United States